The Dynamicity of The Perceptive Verb Look: A Cognitive Linguistics Study - Prayudha Prayudha (Universitas Ahmad Dahlan, 2018)
Perceptive verbs have important function, especially in Cognitive Linguistics perspective, because these verbs are directly related to real experience. Cognitive linguistics focuses on the study of the relationship between language, mind, and socio-physical experience. Thus, this paper discusses how the lexical-semantic characteristics particularly the dynamicity or aktionsarten of the verb look. The verb look itself consists of agentive and perceptive verb class. The dynamicity of agentive and the perceptive verb look were analyzed using the distributional method combined with several techniques. Most of the verb look constructions appear as phrasal verbs. At least, there are 17 phrasal verbs with look as the root and the constructions consist of at least 20 different meanings. The dynamicity test is also applicated for the phrasal verbs. The results of the research show unique lexical characteristics of the perceptive verb look and it influences the meaning as well as the construction of the verb. The relationship between lexical characteristic with its construction shows the schema of cognition processing language.